Malignant fibrous histiocytomas of salivary glands. Issue 9 (September 1982) - Benjamin, E; Wells, S; Fox, H; Reeve, NL; Knox, F
Abstract : The light microscopic, immunohistological and ultrastructural findings in two cases of malignant fibrous histiocytoma arising in salivary glands are presented and the features of seven previously reported cases are reviewed. This neoplasm is extremely rare in this site and may pose problems in diagnosis. It has to be distinguished from other spindled cell tumours, in particular from epithelial tumours of predominantly spindled cell pattern; immunohistological markers for histiocytic cells may be of value. The histogenesis of this neoplasm is controversial but our electron microscopic findings support an origin from mesenchymal cells which differentiate along a broad fibrohistiocytic spectrum.